Peter and Paul Church in the village of Nagorny Ishtan, Tomsk region - Bode, Andrey; Petrova, Svetlana; Salimova, Marina; Salimov , Alexey (project baikal, 2023)
The Peter and Paul Church built in 1872 in the village of Nagorny Ishtan is one of the most famous monuments of wooden architecture in Siberia. The article reveals the history of the settlement, the construction history of the church, determines the original architectural appearance and the appearance of the second construction stage. The article also presents the project of the architect E. E. Eremeev, according to which the temple was built in Nagorny Ishtan. The features of the architecture of the monument under study are revealed. The architectural, artistic and stylistic characteristics of the Peter and Paul Temple are formulated. The architecture and structures of the church, like many buildings of the XIX century, combine traditional forms of wooden architecture and new stylistic influences. The complex scientific surveys of the object made it possible to evaluate the options for the restoration solution and the validity of the optimal solution for the preservation of the Peter and Paul Church.